Peptides from Cauliflower By-Products, Obtained by an Efficient, Ecosustainable, and Semi-Industrial Method, Exert Protective Effects on Endothelial Function. (6th February 2019) - Caliceti, C.; Capriotti, A. L.; Calabria, D.; Bonvicini, F.; Zenezini Chiozzi, R.; Montone, C. M.; Piovesana, S.; Zangheri, M.; Mirasoli, M.; Simoni, P.; Laganà, A.; Roda, A.
Abstract : The large amount of cauliflower industry waste represents an unexplored source of bioactive compounds. In this work, peptide hydrolysates from cauliflower leaves were characterized by combined bioanalytical approaches. Twelve peptide fractions were studied to evaluate unexplored biological activities by effect-based cellular bioassays. A potent inhibition of intracellular xanthine oxidase activity was observed in human vascular endothelial cells treated with one fraction, with an IC50 = 8.3 ± 0.6   μ g / m l . A different fraction significantly induced the antioxidant enzyme superoxide dismutase 1 and decreased the tumor necrosis factor α -induced VCAM-1 expression, thus leading to a significant improvement in the viability of human vascular endothelial cells. Shotgun peptidomics and bioinformatics were used to retrieve the most probable bioactive peptide sequences. Our study shows that peptides from cauliflower waste should be recycled for producing valuable products useful for the prevention of endothelial dysfunction linked to atherogenesis progression.